To Sicily with love - Probst, Jennifer (Meet me in italy, 2025)
"Aurora York had it all together: loving parents, a steady relationship, and a promising career. But after she loses both parents unexpectedly, she can't seem to stay on track any longer. Lonely and lost after a public meltdown that threatens her professional credibility, she's shocked when DNA test results show a blood relative in Sicily. When her cousin reaches out online and begs her to come to Italy to meet everyone in person, Aurora makes the leap. Aurora arrives in Sicily for a month, and there she meets a colorful, dynamic family steeped in tradition. The younger generation is fascinated by her social media fame in America and even though her grandparents have more traditional viewpoints, Aurora begins to heal from her grief...and enjoys the attention of a kind and handsome Italian man. But when the summer ends, a new opportunity calls her back to the States and her old habits threaten to reemerge. Will Aurora leave everything in Sicily she loves behind, or take the chance on a whole new future?"--